Local Open Government Issues in Austin, United States - Erdayani, Rizki; Afandi, Syed Agung; Afandi, Muslim; Arza, Rhaka A. (Institut Pemerintahan Dalam Negeri (IPDN), 2025)
This study aims to analyze key issues of open government in Austin. Austin plays a major role in the United States as the only local government pilot program established by the Open Government Partnership. Qualitative approaches and bibliometric analysis methods are used in this study. The research data were obtained from the official website of the Austin Government and sourced from the Google Scholar database. The findings of this study indicate that the study of Austin's open government is not popular. The topics that dominate the study of Austin's open government are information, collaboration, transparency, communication, development, community, access, framework, service, and communication model. Meanwhile, the latest and potential topics in the study of Austin's open government include network, media, online information, consultative process, implementation, data sovereignty, governance, monitoring, assessment, deployment, infrastructure, data sharing, digital intervention, and innovation strategy. Austin is currently focusing on four main commitments, namely the community climate resilience pilot, inclusion in court contracting, public participation in city anti-displacement efforts, and public safety data analysis. These commitments have the potential to create a more open Austin government.